2015
DOI: 10.1002/2014jd022375
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure and physical processes of the Madden‐Julian oscillation: Exploring key model physics in climate simulations

Abstract: Aimed at reducing deficiencies in representing the Madden-Julian oscillation (MJO) in general circulation models (GCMs), a global model evaluation project on vertical structure and physical processes of the MJO was coordinated. In this paper, results from the climate simulation component of this project are reported. It is shown that the MJO remains a great challenge in these latest generation GCMs. The systematic eastward propagation of the MJO is only well simulated in about one fourth of the total participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
417
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 340 publications
(440 citation statements)
references
References 206 publications
(336 reference statements)
19
417
4
Order By: Relevance
“…1c), so that both lead the major precipitation (and the mid-level maximum upward motion). This vertical backward structure is consistent with many previous observational studies (e.g., Sperber 2003;Tian et al 2006;Jiang et al 2015).…”
Section: Observed and Model Simulated Mjosupporting
confidence: 81%
See 2 more Smart Citations
“…1c), so that both lead the major precipitation (and the mid-level maximum upward motion). This vertical backward structure is consistent with many previous observational studies (e.g., Sperber 2003;Tian et al 2006;Jiang et al 2015).…”
Section: Observed and Model Simulated Mjosupporting
confidence: 81%
“…1). We examined 24 GCMs participated in MJOTF/GASS Global Model Evaluation Project (Jiang et al 2015). Figure 1 (upper panels) shows propagation and structure of the observed MJO.…”
Section: Observed and Model Simulated Mjomentioning
confidence: 99%
See 1 more Smart Citation
“…Sperber et al (2005) indicated that realistic description of mean state is important for better simulation of MJO, while Kim et al (2011), Benedict et al (2013) and Boyle et al (2015) found that improved representation of MJO may corresponds to degraded mean state in one or more aspects in models. By comparing several models, Jiang et al (2015) showed an insignificant link between model MJO fidelity and mean state, which suggests that some factors other than the mean state are critical for realistic simulation of MJO. Klingaman et al (2015a, b) further showed that there is little correspondence between the MJO fidelity in model simulation and the MJO skill in initialized forecasts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…(2) To what extent can the MJO prediction skill be enhanced by reducing the error in MJO simulation? Studies by Jiang et al (2015), Klingaman et al (2015a, b), and Xavier et al (2015) characterized the key features in MJO physics and further examined how these features were related to models' MJO simulation and forecast skills. They showed weak and statistically insignificant relationships between MJO fidelity in the free-run simulations and initialized hindcasts.…”
Section: Introductionmentioning
confidence: 99%